2020
DOI: 10.1042/bsr20193794
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MCM3AP-AS1 inhibits cell proliferation in cervical squamous cell carcinoma by down-regulating miRNA-93

Abstract: Background: MCM3AP antisense RNA 1 (MCM3AP-AS1) is characterized as an oncogenic lncRNA in hepatocellular carcinoma and glioblastoma. We analyzed TCGA dataset and observed the down-regulation of MCM3AP-AS1 in cervical squamous cell carcinoma (CSCC). The present study was therefore performed to investigate the role of MCM3AP-AS1 in CSCC. Methods: A total of 64 female patients with CSCC (38–68 years old; mean age: 53.1 ± 6.5 years old) were enrolled in the present study. RT-qPCR was performed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Therefore, we speculated that MCM3AP-AS1 may play oncogenic roles in cancer biology mainly by serving as a ceRNA of tumor suppressive miRNAs. In addition, a recent study showed that MCM3AP-AS1 was downregulated in cervical cancer and it could downregulate miR-93 to inhibit cell proliferation in cervical cancer [15]. Therefore, MCM3AP-AS1 may play different roles in different cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we speculated that MCM3AP-AS1 may play oncogenic roles in cancer biology mainly by serving as a ceRNA of tumor suppressive miRNAs. In addition, a recent study showed that MCM3AP-AS1 was downregulated in cervical cancer and it could downregulate miR-93 to inhibit cell proliferation in cervical cancer [15]. Therefore, MCM3AP-AS1 may play different roles in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lncRNAs are potential targets for cancer treatment [11]. LncRNA MCM3AP Antisense RNA 1 (MCM3AP-AS1) plays an oncogenic role in several types of cancer, such as hepatocellular carcinoma, papillary thyroid cancer, glioblastoma, and cervical cancer [12][13][14][15]. It has been well established that MCM3AP-AS1 participates in cancer biology mainly by sponging tumor suppressive miR-NAs to upregulate oncogene expression [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, MCM3AP‐AS1 is overexpressed in prostate cancer, and it modulates the methylation of NPY1R promoter via the recruitment of DNMT1/DNMT3, thereby enhancing the multiplication, migration and invasion of cancer cells 22 . However, MCM3AP‐AS1 expression is down‐regulated in cervical squamous cell carcinoma and its reduction is associated with poor survival; functional experiments show that MCM3AP‐AS1 inhibits the multiplication of cells by inhibiting miR‐93 expression 23 . Previously, there have been no reports about the expression pattern, biological function and underlying mechanism of MCM3AP‐AS1 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-93 can regulate many cancers, but, to our knowledge, there are no reports on its effects on bovine fat development. 16 , 17 Cioffi et al. reported that miR-93 controls obesity by inhibiting Sirt7 and Tbx3.…”
Section: Discussionmentioning
confidence: 99%